General pediatrics board review - Yazdani, Shahram; Kamzan, Audrey; Kulkarni, Deepa; Lerner, Carlos; Newcomer, Charles A. (New York, NY : Oxford University Press, 2020)
'General Pediatrics Board Review' is a comprehensive guide for recent residency graduates and re-certifiers preparing for the American Board of Pediatrics (ABP) board exam. The text consists of over 1000 multiple-choice questions, organized into 25 chapters covering pediatrics topics such as fetal and neonatal care, adolescent and young adult medicine, genetics, child maltreatment, pediatric infectious diseases, gastrointestinal disorders, and more. Chapters include questions, answers with detailed explanations, and references to primary or landmark articles to help better navigate a standardized exam. Questions are written in a case-based format that emulates the ABP board exam, and are supplemented by figures, tables, and boxes. A quick facts section helps to emphasize important and frequently tested information.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 3, 2020).
Keywords: Pediatrics -- Examinations -- Study guides; American Board of Pediatrics -- Examinations -- Study guides